Teaching multiple approaches to management to facilitate prosocial and environmental well-being. Issue 1 (February 2022) - Dyck, Bruno; Caza, Arran
Friedman's maxim "The social responsibility of business is to increase its profits" (p. 32) has shaped what managers consider effective management. This Financial Bottom Line approach to management has been challenged by both Positive Organizational Scholarship (POS) and Critical Management Studies (CMS). POS highlights how enhancing prosocial and other nonfinancial considerations can increase profits, consistent with the current dominant Triple Bottom Line approach. In contrast, CMS tends to critique any approach that seeks to maximize profits by creating dysfunctional power symmetries and marginalization. This study introduces a third option, the Social and Ecological Thought approach, which promotes maximizing social and ecological well-being while remaining financially viable. A longitudinal pre-post intervention in a sample of undergraduate management students showed that teaching multiple approaches to management—Financial Bottom Line, Triple Bottom Line, and Social and Ecological Thought—resulted in learners becoming less likely to espouse profit-related goals (e.g. to maximize efficiency, productivity, profitability) and more likely to identify nonfinancial ones (e.g. extra-organizational prosociality and reduction of marginalization) when characterizing effective management. However, the results did not support predictions regarding intra-organizational prosociality and marginalization, or power asymmetries. We discuss implications for pedagogy and the future development of POS and CMS.